The horror film genre as an interpretive device in an adaptation of Tennessee Williams 's Suddenly last summer - Kirlew, Akil (Centre for Film and Media Studies, 2016)
As my thesis, I have made an adaptation for film of Suddenly Last Summer by Tennessee Williams. The play tells the story of a young woman, Catharine Holly, who has been institutionalized shortly after her return to New Orleans from a vacation on the island of Cabeza de Lobo. Her cousin, Sebastian, a wealthy poet and gay sex-tourist died on this trip. He was killed and partially eaten by a group of impoverished young men (at least some of these men were his former sexual partners). Sebastian's mother, Violet Venable - in the hopes of suppressing the true circumstances surrounding the death of her son - attempts to persuade an ambitious young doctor to lobotomize Catharine as the play opens. It should be noted that the horror film genre has greatly affected my thinking about this project, and I will be discussing three sub-genres of horror at some length: body horror, the slasher film, and race horror. The horror films and trends to be discussed come, in the main, from the period ranging from the late 1970s to the early 1990s and will, I think, be of great help in explaining certain choices I have made in the course of making this film. My main interest is determining whether the themes present in Williams's original text can be explored and expanded upon via recourse to the horror genre. Additionally, my film moves the action of Suddenly Last Summer from the New Orleans of the early half of the twentieth century to modem-day Cape Town. However, the action takes place in a sort of netherworld or blank space that serves as metaphor for both cinema and the white cube of the gallery. This choice of staging is meant to refer to Catharine's mention of the "blazing white wall" against which her cousin's body was thrown after his death. In fact, all throughout Catharine's description of how and why Sebastian died-and it must be remembered that it is this description that serves as the denouement of the play-mentions of white light, white heat, Sebastian's whiteness (as opposed to simply saying he looked pale), and the whiteness of the day itself are employed as a sort of leitmotif That Catharine uses "whiteness" in describing an incredibly violent chapter in her past is crucial to my understanding of the text and has helped me craft a cinematic strategy for my adaptation of this play. The violence and savagery that has marked Catharine's past has followed her into the present, just as it has followed her from the impoverished island of Cabeza de Lobo to the wealthy Garden District of New Orleans, and-if Violet Venable has her way-it will follow Catharine into her future. Taking the key descriptive element of that violent day in Cabeza de Lobo and using it to paint the world of Catharine's present will, I hope, make this connection clear.